WRITING SKILL AS A CORE COMPONENT OF TRANSLATION COMPETENCE (Scientific Conference on Multidisciplinary Studies, 2025)
This article explores the role of writing skills as a fundamental component of translation competence. It argues that proficiency in written expression is not only essential for the accurate and coherent transfer of meaning from one language to another, but also for ensuring stylistic adequacy and communicative effectiveness. The discussion highlights how writing competence interacts with other sub-competencies, including linguistic, cultural, and pragmatic knowledge, and examines its integration into translator training programs. Emphasis is placed on the necessity of teaching writing techniques, genre awareness, and text structuring to future translators, especially in academic contexts. The paper concludes that without well-developed writing skills, translation quality suffers, making writing training a priority in professional translator education.